Drainage tube hole suture improvement: Removal‐free stitches. Issue 9 (31st July 2019) - Fu, Rui; Zhang, Jia‐Tao; Dong, Song; Chen, Ying; Zhang, Chao; Tang, Wen‐Fang; Xia, Jin; Nie, Qiang; Zhong, Wen‐Zhao
Abstract : Surgical method improvements aim to optimize the patient experience. The problem of healing of the drainage tube hole has not received attention and is of concern because it can plague patient recovery. In this article we report on how we have improved the method of suturing the drainage tube hole and explore the safety and effectiveness of this method. Between December 2017 to August 2018, 102 patients underwent thoracoscopic lung resection (single port or single utility port) using different methods of suturing drainage tube holes. The intervention group received improved methods with subcuticular and intradermal suture and removal‐free stitches, whilst the control group received a conventional mattress suture and fixed chest tube. A preset line was left to tie knots and close the hole after the removal of the chest tube. The stitches were removed 7–12 days after surgery. The baseline clinical features of the patients were subsequently analyzed. The objective and subjective conditions of scars were evaluated using the Vancouver Scar Scale (VSS) and the Patient and Observer Scar Assessment Scale (POSAS) at one month after surgery. The intervention group ( n = 71) and control group ( n = 31) had balanced baseline clinical characteristics. There were no significant differences between the two groups in terms of three‐day postoperative pain and postoperative hospital stay. In the intervention group, three patients (4.23%) had wound splitting that required re‐suturing, which was better than five patients (16.13%) in the control group ( P  < 0.05). The incidence of pleural fluid outflow, wound infection, post‐removal pneumothorax, chest tube prolapse and incisional hernia were not different between the two groups. We conclude that the objective and subjective evaluation results of scars were significantly different between the two groups ( P < 0.05), and the experimental group was superior to the control group. A balanced result between aesthetic appearance and safety as regards video‐assisted thoracic surgery can be achieved through the chest tube hole improved suture method. This method also improves the patient's recovery experience.